Desenvolvimento de uma interface web para a plataforma DIVERGENOME: uma ferramenta bioinformática para estudos de genética de populações e epidemiologia genética - Marcia Lobao Iannini (2010)
The DIVERGENOMEdb bioinformatics platform consists of a relational database which allows the user to organize and gather a series of genetic and phenotypic information from multiple population genetics and genetic epidemiology projects. DIVERGENOMEdb facilitates to share data obtained from scientific research through a system that allows to enter new information and access the database quickly and simply. With this purpose, we built a graphical interface for the relational database DIVERGENOMEdb. We used the programming language HTML, PHP and JavaScript embedded. The platform used was the Linux / Intel and the application was hosted on an Apache server. With the developed interface the users can perform many kinds of data queries using filters, and enable registered users to insert scientific data in DIVERGENOMEdb without the need of previous knowledge of SQL command lines. Keywords: